Abstracts from XIII PPGCF Meeting - Federal University of Rio Grande do Sul (UFRGS) - - PPGCF - UFRGS, Pharmaceutical Sciences Graduate Program (Drug Analytical Research, 2021)
The PPGCF was a pioneer among the Programs in the Brazilian Pharmacy area in the creation of an annual internal event, which began in 2009 with the purpose of bringing together all the staff of the Program to discuss the research results generated, beside to enrich the scientific and technological knowledge based on lectures given by national and international researchers. The XIII Meeting of the Pharmaceutical Sciences Graduate Program of UFRGS with the theme: "THE ROLE OF PHARMACEUTICAL SCIENCES ON THE FRONTIER OF INNOVATION", was held on December 6th and 7th, 2021 (https://www.ufrgs.br/encontroppgcf2021/#sobre-o-xiiiencontroppgcf). The event was held remotely with live broadcast on YouTube.